Movement analysis of match play in U16-U21 youth Hungarian soccer players - the influence of age, position, and contextual variables - Kádár, L.; Géczi, G.; Bognár, J.; Csáki, I. (International Journal of Performance Analysis in Sport, 2023)
The purpose of this study was to demonstrate the locomotor match-performance of youth Hungarian football players according to age groups, playing positions and effects of contextual match factors. The sample consisted of 574 individuals in four youth age groups (U16, U17, U19, U21) in four playing positions: central defenders (n = 139), fullbacks (n = 148), central midfielders (n = 185), and forwards (n = 102). Tactically, all teams used a 4-4-2 diamond formation. Data was collected from 114 matches from elite Hungarian football academy matches during the 2018-2019 season, using a GPS technology (10 Hz). The main results were: (a) U16, U19, U21 age groups matches played against strong opponents presented greater values (but not significantly) of high-intensity running distances compared to matches against weak opponents; (b) U21 players covered greater high-intensity running distances when winning than drawing the matches; (c) the U16, U19, U21 age groups performed better (but not significantly) at home than away in terms of high-intensity running. The forwards (735 ± 176 m) and fullbacks (654 ± 185 m) performed best in total high-intensity running (>19.8 km/h). With regard to maximum speed, forwards reached significantly higher results (30.44 ± 1.64 km/h) than players in other positions. Since international football players demonstrate better measures in high-intensity running and sprinting than Hungarian players.